2008
DOI: 10.1038/modpathol.2008.36
|View full text |Cite
|
Sign up to set email alerts
|

The COX-2 promoter polymorphism –765 G>C is associated with early-onset, conventional and stump gastric cancers

Abstract: COX-2 overexpression is known to be an important mechanism in gastric carcinogenesis. Previously we have found that early-onset gastric cancer has a unique COX-2 low-expressing phenotype that differs significantly from that of the frequent overexpression seen in conventional gastric cancers. To investigate whether the COX-2 -765 G4C promoter polymorphism (known to lead to a reduction of COX-2 promoter activity in the colon) may explain this difference in expression, we carried out single-nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
4
21
3
Order By: Relevance
“…This result is consistent with that of Liu et al (13) but differs from findings of studies performed in the populations of The Netherlands and India (14,15). In a study by Sitarz et al, COX-2-765G allele promoter polymorphism was found to be significantly associated with gastric cancer in The Netherlands (14). However, Saxena et al (15) reported that the frequency of the C carrier has a significant association with gastric adenocarcinoma.…”
Section: First-degree Relatives Second-degree Relatives -------------contrasting
confidence: 51%
See 2 more Smart Citations
“…This result is consistent with that of Liu et al (13) but differs from findings of studies performed in the populations of The Netherlands and India (14,15). In a study by Sitarz et al, COX-2-765G allele promoter polymorphism was found to be significantly associated with gastric cancer in The Netherlands (14). However, Saxena et al (15) reported that the frequency of the C carrier has a significant association with gastric adenocarcinoma.…”
Section: First-degree Relatives Second-degree Relatives -------------contrasting
confidence: 51%
“…However, COX-2-765G>/C polymorphism failed to exhibit an association with gastric cancer in this study, and there was no significant correlation between the first-and second-degree relatives and COX-2-765 genotypes. This result is consistent with that of Liu et al (13) but differs from findings of studies performed in the populations of The Netherlands and India (14,15). In a study by Sitarz et al, COX-2-765G allele promoter polymorphism was found to be significantly associated with gastric cancer in The Netherlands (14).…”
Section: First-degree Relatives Second-degree Relatives -------------contrasting
confidence: 39%
See 1 more Smart Citation
“…In particular, increased COX-2 expression is linked to progression of gastric cancer and precancerous tissues by activating angiogenesis, inhibiting apoptosis, and accelerating invasion and metastasis (Murata et al, 1999;Uefuji et al, 2000;Ohno et al, 2001;Tatsuguchi et al, 2004). Genetic variants, such as single nucleotide polymorphisms (SNPs) in the promoter region of the COX-2 encoding gene, which features guanine (G) converting to cytosine (C) at position -765 bp of the promoter region, affecting transcription activity of -765G>C (rs20417) polymorphism of COX-2 and its functional activity (Szczeklik et al, 2004;Sitarz et al, 2008).…”
Section: Research Articlementioning
confidence: 99%
“…Genotype and allele distributions for each case-control study are shown in Table 2. There were 6 case-controls of Asians (Liu et al, 2006;Tang et al, 2009;Li et al, 2012;Shin et al, 2012), 2 of Caucasians (Pereira et al, 2006;Hou et al, 2007), 1 Indians (Saxena et al, 2008) and 1 Dutch (Sitarz et al, 2008). All the included 8 eligible reports were written in English and 2 were written in Chinese language.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%